2020
DOI: 10.17509/ijal.v9i3.23202
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian EFL teachers’ content conceptualization and course organization: A portray of text-based teaching

Abstract: Frequent changes of Indonesian English as a Foreign Language (EFL) national curriculum have transformed EFL teachers’ role from that of serving merely as curriculum transmitters into curriculum adapters. Accordingly, this study intended to explore how a group of Indonesian EFL teachers conceptualize content and course organization as guided by the Indonesian national EFL curriculum. A qualitative multiple-case study (Miles, Huberman, Saldana, 2014; Stake, 2006; Yin, 2014) was employed to collect and analyze d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The other common problems that the teachers faced were selecting texts, adapting or modifying texts, designing tasks, and overcoming students' boredom. This finding is similar to previous studies that the problem in implementing a text-based approach was that the English teacher lacked in-depth conceptual and practical knowledge (Mohlabi-Tlaka, 2016;Triastuti & Riazi, 2020). The common problems faced by the teachers are clarified as follows.…”
Section: Common Problems Faced By Efl Teachers In Implementing Text-based Teachingsupporting
confidence: 88%
See 1 more Smart Citation
“…The other common problems that the teachers faced were selecting texts, adapting or modifying texts, designing tasks, and overcoming students' boredom. This finding is similar to previous studies that the problem in implementing a text-based approach was that the English teacher lacked in-depth conceptual and practical knowledge (Mohlabi-Tlaka, 2016;Triastuti & Riazi, 2020). The common problems faced by the teachers are clarified as follows.…”
Section: Common Problems Faced By Efl Teachers In Implementing Text-based Teachingsupporting
confidence: 88%
“…A qualitative multiple-case study revealed the difficulties of implementing text-based teaching methods in selecting and organizing texts for teaching. It was recommended that the teachers be trained with the conceptual and practical knowledge of text-based teaching (Triastuti & Riazi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Given the strengths of GBT, many English teachers have found that translating the GBT methodology into contextual classroom practices within particular socio-educational context is challenging (see Kartika-Ningsih & Gunawan, 2019;Racelis & Matsuda, 2013;Tardy, 2017Tardy, , 2019Triastuti & Riazi, 2020). In Indonesia, the 2013 Indonesian EFL Curriculum has required Indonesian EFL teachers to teach several genres, as explicitly stated in the formulations of the basic competences of the curriculum, while integrating the mandated contents, consisting of character values, higher order thinking skills (HOTS) and the 21st century learning skills, including 4Cs (communication, collaboration, critical thinking and creativity), into their instruction.…”
Section: Introductionmentioning
confidence: 99%
“…This unclear direction is evident in teachers' confusion in putting GBT into practice since the inclusion of GBT in the 2006Curricula (Departemen Pendidikan Nasional, 2004Kemendikbud, , 2016. Teachers' GBT practices within these last two EFL curricula have indicated the partial implementation of GBT in which genres and the following text types, and the GBT methodology are used as the venue for mainly teaching micro and macro skills of English, and mismatches between the GBT methodology and other influencing methods collide (Kartika-Ningsih & Gunawan, 2019;Triastuti & Riazi, 2020). This condition, therefore, suggests the provision of a GBT model for guiding teachers to properly enact GBT practices within the GBT methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in language education are interested in factors that promote the development of language skills in general (e.g., [26,27]), and life skills in particular (e.g., [28]). Project-based learning could be one of these factors as, according to social constructivist theory, learning a language is a social and dynamic process that emphasizes the occurrence of learning when learners interact with each other.…”
Section: Project Based Learning In the Language Classroommentioning
confidence: 99%